TECHNOLOGY FOR DEVELOPING CRITICAL THINKING THROUGH BIOLOGICAL MODELING TECHNOLOGIES IN MEDICAL EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article highlights teaching technologies based on modeling biological problems in the process of medical education. Through this approach, students not only gain theoretical knowledge but also develop skills in deeply analyzing complex biological processes, applying them in practice, developing critical thinking, and solving problems. Modeling technologies play a crucial role in improving the quality of education and training medical professionals. In addition, the article analyzes effective methods for developing critical thinking and their integration into the educational process.